Investigation of Tribological Performances for Porous Structure of Diatom Frustule with FSI Method - Fanming Meng; Guixiang Gao; TingTing Li (Advances in Condensed Matter Physics)
Tribological performances of the diatom frustule are investigated with the liquid-solid interaction (FSI) method. Take, for example, the representative Coscinodiscus sp. shell; the diatom frustule with the porous structure is achieved by the scanning electron microscope (SEM). Based on the frustule, the representative diatom frustule is modeled. Further, tribological performances of the diatom at its different geometry sizes and velocities are solved with FSI method and compared with corresponding values for the nonporous structure. The numerical result shows that the existence of the porous structure of the diatom helps to reduce friction between it and ambient water and to increase its load-carrying capacity.